From Tradition to Transformation: The Role of Accreditation in Improving the Quality of Education in Islamic Boarding Schools - Ummi Hani’; Holifah; Fatimatul Husna; Misbahul Arifin (Education Research Center, 2025)
This study explores the role of accreditation, specifically the implementation of ISO 21001:2018, in enhancing educational quality at Islamic boarding school Nurul Jadid, Paiton, Probolinggo. Using a qualitative approach with a case study design, data were collected through observation, interviews, and documentation over a seven-day field study. The analysis employed the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The findings reveal that accreditation not only improved administrative systems and documentation but also significantly influenced human resource attitudes, organizational culture, and public perception of the institution. The integration of quality standards contributed to greater institutional accountability, professionalism, and internal collaboration. Moreover, the pesantren’s ability to maintain its traditional Islamic values while adopting international quality frameworks demonstrates that transformation and tradition can coexist harmoniously. This research provides new insights into how quality assurance systems can be contextualized in religious-based education and offers a model for other Islamic institutions seeking sustainable reform.